Isoeugenol affects expression pattern of conidial hydrophobin gene RodA and transcriptional regulators MedA and SomA responsible for adherence and biofilm formation in Aspergillus fumigatus - Gupta, Lovely; Sen, Pooja; Bhattacharya, Asish K.; Vijayaraghavan, Pooja (Archives of Microbiology, 2022)
Aspergillus fumigatus is one of the major pathogenic fungal species, causing life-threatening infections. Due to a limited spectrum of available antifungals, exploration of new drug targets as well as potential antifungal molecules has become pertinent. Rodlet layer plays an important role in adherence of fungal conidia to hydrophobic cell surfaces in host, which also leads to A. fumigatus biofilm formation, contributing factor to fungal pathogenicity. From decades, natural sources have been known for the development of new active molecules. The present study investigates effect of isoeugenol on genes responsible for hydrophobins (RodA), adhesion as well as biofilm formation (MedA and SomA) of A. fumigatus. Minimum inhibitory concentrations (MIC and IC50) of isoeugenol against A. fumigatus were determined using broth microdilution assay. The IC50 results showed reduced hydrophobicity and biofilm formation as well as eradication after treatment with the compound and electron micrograph data corroborated these findings. The qRT-PCR showed a significant downregulation of genes RodA, MedA, SomA and pksP involved in hydrophobicity and biofilm formation. SwissADME studies potentiated drug-like propensity for isoeugenol which formed four hydrogen bonds with low binding energy (- 4.54 kcal/mol) at the catalytic site of RodA protein studied via AutoDock4. Hence, the findings conclude that isoeugenol inhibits conidial hydrophobicity and biofilm formation of A. fumigatus and further investigations are warranted in this direction.
Keywords: Aspergillus fumigatus; Hydrophobicity; Isoeugenol; Transcription regulators; Virulence